DIGITAL NOTE-TAKING PRACTICES IN ONLINE ENGLISH READING AMONG ENGLISH EDUCATION STUDENT - Natasha Ika (Jurnal Ilmiah Spectral, 2026)
This study examines digital note-taking practices among English Education students at Universitas Tanjungpura when reading online English texts. Although digital note-taking has grown alongside the increasing use of digital learning materials in higher education, few studies have specifically looked at how students apply these strategies during online reading activities. This study aimed to describe the frequency and types of digital note-taking practices used by English Education students while reading online English texts. A descriptive quantitative design was employed, involving 30 students selected through convenience sampling. Data were collected using an 18-item questionnaire distributed via Google Form, measured on a five-point Likert scale. The results show that most students frequently read English texts online, with 46.7% doing so very often, mostly through smartphones (86.7%). Highlighting important information was the most commonly used note-taking strategy (66.6%), followed by saving information for later review (70%). Typing short notes was practiced less consistently. The majority of students (80%) agreed that digital note-taking helps them remember information from online texts. Overall, students showed moderate engagement in digital note-taking and tended to rely on simpler strategies. These findings suggest that students may benefit from structured guidance on using more varied digital note-taking strategies to better support their comprehension when reading online academic texts.